Inactivating mutations in genes encoding for components of the BAF/PBAF complex and immune-checkpoint inhibitor outcome - Kevin Courtet; Yec'han Laizet; Carlo Lucchesi; Alban Bessede; Antoine Italiano (BMC, 2020)
Abstract Alterations of genes encoding subunits of the BAF/PBAF complexes are among the most frequent gene aberrations in human cancer. Such alterations have been shown to have an impact on tumor microenvironnement and on the capacity of tumors to respond to immune-checkpoint inhibitors (ICI). We analysed the clinical and genetic data from 43,728 patients accessed through cBioportal. The mutational frequencies of ARID1A, ARID1B, ARID2, PBRM1, SMARCA4, and SMARCB1 were 6.6%, 3,4, 3.4, 3.2, 4.1, and 1.2%, respectively. We then investigated the association between the presence of least one nonsynonymous somatic mutation of ARID1A, ARID1B, ARID2, PBRM1, SMARCA4, or SMARCB1 and overall survival of 1661 patients treated with an ICI. Across the entire cohort, patients with BAF/PBAF mutated tumors have a statistically significant improvement in overall survival (median overall survival: 28 months [95% CI 21.6-34.3] versus 15 months [95% CI 12.9-17.0], p < 0.0001). When tumor mutational burden was adjusted for a multivariable Cox regression analysis, BAF/PBAF gene mutations remained an independent prognostic factor for overall survival in patients treated ICI. Our results establish a relationship between mutations in key genes encoding for components of the BAF/PBAF complex and outcome of patients treated with ICI. Further studies are needed to elucidate the underlying mechanisms of this interaction.